Optimization of kitchen scale design by using Boothroyd-Dewhurst DFA method - Muhammad Asyraf, Mohd Niza (2009)
This thesis deals with design optimization of existing produt (kitchen scale) for better improvement by using Boothroyd-Dewhurst Design for Assembly (DFA) Methodology. The objective of this thesis is to generate a new design of kitchen scale that consider the matter of parts elimination, cost estimation, and design efficiency (DE). The thesis describes the Boothroyd-Dewhurst DFA method in obtaining the suggestion for redesign of the parts evaluated. The strategy of evaluating the existing design is first to choose the available product in the market in order to solve a problem. The product choosen were then disassembled into several families or sub-assemblies. This is for understanding how the parts functioning during normal operating mode. After that, each parts been critics and study if there is a chances for redesign. Finally, referring to suggestion from Boothroyd-Dewhurst DFA method, the new parts design are generated. From the results, it is observed that the analysis using Boothroyd-Dewhurst DFA method is easier for determine the parts to be redesign. The acquired results utilizing the new design are much more efficient then the original design after the evaluation due to maximum reduction of components like screw and fasteners. However, reducing the parts not always meant that the design are being optimize. There are much more things to consider like the manufacturing process required to produce the new design. Therefore, the concept of concurrent engineering (CE) is important to have designers and production engineers way of thinking in redesigning the new parts or components.